Short-Term Oral Magnesium Supplementation Suppresses Bone Turnover in Postmenopausal Osteoporotic Women - YAVUZ, DİLEK; GÖZÜ, HÜLYA (HUMANA PRESS INC, 2010)
Magnesium has been shown to increase bone mineral density when used in the treatment of osteoporosis, yet its mechanism of action is obscure. In this study, the effects of daily oral magnesium supplementation on biochemical markers of bone turnover were investigated. Twenty postmenopausal women have been divided into two groups. Ten patients were given magnesium citrate (1,830 mg/day) orally for 30 days. Ten postmenopausal women of matching age, menopause duration, and BMI were recruited as the control group and followed without any medication. Fasting blood and first-void urine samples were collected on days 0, 1, 5, 10, 20, and 30, respectively. Total magnesium, calcium, phosphorus, iPTH and osteocalcin were determined in blood samples. Deoxypyridinoline levels adjusted for creatinine were measured in urine samples. Thirty consecutive days of oral magnesium supplementation caused significantly decrease in serum iPTH levels in the Mg-supplemented group (p < 0.05). Serum osteocalcin levels were significantly increased (p < 0.001) and urinary deoxypyridinoline levels were decreased (p < 0.001) in the Mg-supplemented group. This study has demonstrated that oral magnesium supplementation in postmenopausal osteoporotic women suppresses bone turnover.
Keywords: Postmenopausal osteoporosis; Magnesium; Bone turnover; BIOCHEMICAL MARKERS; MINERAL CONTENT; METABOLISM; DEFICIENCY; ALENDRONATE; FRACTURE; CALCIUM; MOUSE; RATS; MASS